Experimental study on low thermal conductive and flame retardant phase change composite material for mitigating battery thermal runaway propagation. (March 2022) - Niu, Junyi; Deng, Suyun; Gao, Xuenong; Niu, Huichang; Fang, Yutang; Zhang, Zhengguo
Highlights: A low thermal conductive PCM with flame retardant coating (FR-CPCM) was prepared. Flame retardance of FR-CPCM was V-0 in UL-94 vertical burning test. FR-CPCM exhibited good compressive performance. FR-CPCM performed better thermal insulation than aerogel blanket and ceramic fiber. FR-CPCM contributed to the mitigation of battery thermal runaway propagation. Abstract: Lithium-ion batteries (LIBs) have dominated the market in portable electronics, electric vehicles, and aerospace applications. However, safety issues greatly limit the further applications of LIBs. In this work, a low thermal conductive phase change composite material (CPCM) with flame retardant coating (FR-CPCM) is proposed, which is placed between batteries to prevent thermal runaway (TR) propagation. The CPCM with 40 wt.% paraffin (PA) and 60 wt.% silica aerogel (SA) achieves the lowest thermal conductivity of 0.051 W/(mK) at the density of 424 kg/m 3 . After coated, the FR-CPCM performs the V-0 rating at UL-94 test and 56.31% of limiting oxygen index, as well as a good insulation performance under the nearly 700 °C side heating test. The thermal runaway (TR) tests of battery modules show that the addition of FR-CPCM between batteries can effectively prevent the propagation of battery TR, and keep the maximum external temperature of the adjacent battery below 182.6 °C. While TR in module without FR-CPCM propagated to its adjacent one in only 63 s. Moreover, FR-CPCM exhibits good compressive performance, which will not crack even under the pressure of 40 MPa. The above results indicate that FR-CPCM is promising in the application of safer battery systems. Graphical abstract: Image, graphical abstract